Spirituality and anxiety in pastoral care workers and physicians in the first wave of the COVID-19 pandemic - Culmann, Anna C.; Baranowski, Andreas M.; Matthias, Julia-K.; Tüttenberg, Simone C.; Belschner, Wilfried; Erim, Yesim; Morawa, Eva; Beschoner, Petra; Jerg-Bretzke, Lucia; Albus, Christian; Steudte-Schmiedgen, Susann; Reuter, Martin; et al. (Frontiers in Psychiatry, 2024)
The COVID-19 pandemic had serious impact on the well-being of health care workers and highlighted the need for resources to help hospital staff to cope with psychologically negative consequences. The purpose of this study was to investigate the potentially protective effect of spirituality, as measured by the construct of transpersonal trust, against anxiety in physicians and in hospital pastoral care workers. In addition, transpersonal trust was compared to the effects of other potential resources, namely sense of coherence, optimism, and resilience. We also explored the relationship between transpersonal trust and anxiety and how it was moderated by sense of coherence and expected a significant effect. The sample included N = 405 participants (n = 151 pastoral care workers and n = 254 physicians) who completed an online survey during the first wave of the COVID-19 pandemic between 20th April and 05th July, 2020, that comprised established questionnaires assessing anxiety, transpersonal trust, sense of coherence, and resilience. There was no statistically significant negative relationship between transpersonal trust and anxiety in either profession or broken down by occupational group. Multiple regression analysis revealed that sense of coherence inversely predicted generalized anxiety, while transpersonal trust, resilience, and optimism did not. As hypothesised, the association between transpersonal trust and anxiety was moderated by sense of coherence. However, we could not confirm our hypothesis of a protective effect of transpersonal trust against anxiety. Our results point to the significant role of sense of coherence as a protective factor against anxiety and highlight the complexity of the relationship among spirituality, transpersonal trust, and anxiety.